Femoroiliac thrombectomy - Mazza Bruno, Milton E (Cirugía del Uruguay, 1971)
Femoro-illiac venous thrombectomies are analysed in the following aspects: a) clinical; b) time elapsed since onset; e) phlebographic data; d) existence of thromboembolism; and e) the patient's general condition. The paper also contains an account of the operatory procedure and of the use of Fogarty's catheter.